Financing the Implementation of Performance Budgeting in Local Government Units - the Polish Example of Unised European Union Funds - Kowalska, Iwona (Studia Oeconomica Posnaniensia, 2013)
The financial support of local government units (LGU) in the substantive development of a methodology for performance budgeting is a sine qua non condition for the success of these changes in the approach to public spending. The Human Capital Operational Programme (HCO P) from 2007 to 2013 allocated EU funds for the expert assistance of local governments interested in implementing performance budgeting. The purpose of this article is to demonstrate the inadequate use of opportunities offered by the European Union using the examples of a systemic project as well as competition projects implemented within the Human Capital Operational Programme. The assessment is based on the subject literature, Ministry of Finance materials as well as personal experience being one of the experts for the Polish Ministry of Regional Development for assessing project applications under HCO P Priority V. T he paper also includes recommendations regarding the use of EU funds for the implementation of performance budgeting in local government units in the years 2014-2020.